Perancangan Board Game sebagai Media Edukasi Inklusif untuk Murid Tuli SDN 2 Bengkala dengan pendekatan Design Thinking - Muhammad Garil Zanardi; Garick Gisala Kurnia; Endira Fitriasti Julianda (Universitas Widyatama, 2026)
SDN 2 Bengkala inclusive school needs the role of Visual Communication Design (VCD) to help deaf sixth graders understand solar system material that is difficult to convey due to the lack of scientific terms in Kata Kolok, the local sign language of Bengkala. This study aims to design an educational board game called “Sangkasa” as an inclusive learning medium, utilizing a qualitative-interpretative approach through design thinking and ethnographic methods. Data was obtained from interviews with interpreter teachers, historians, and Kolok students, as well as through focus group discussions and the creation of low-fidelity prototypes. The results of the study show that Sangkasa is effective in helping deaf students understand the characteristics of planets through Kolok sign cards and the Kolok dictionary, while also increasing learning motivation and inclusive interaction between deaf and non-deaf students. Keywords: Kata Kolok, Educational Media, Board Game, Design Thinking, Inclusive School.